EPQ Model for Deteriorating Items with Quadratic Demand, Dynamic Production Rate and Production Time Dependent Selling Price: A Risk Analysis Approach - Nita H. Shah; Mrudul Y. Jani; Urmila Chaudhari (International Journal of Supply Chain Management, 2018)
In this article, a production inventory model with dynamic production rate and production time dependent selling price has been presented. We consider the product with constant deterioration rate which is a very realistic approach. It is also considered that the production rate is a decreasing function of the inverse efficiency of the system. Here, time dependent quadratic demand is deliberated which is suitable for the products whose demand increases initially and subsequently it starts to decrease. Industries like fashion and electronics most probably deals with this type of demand. The main objective is to maximise the total profit with respect to inverse efficiency and total production period. The model is supported with numerical example. Sensitivity analysis is done to derive insights for decision-maker. Graphical results, in two and three dimensions, are exhibited for optimality of the model with supervisory decisions.